Analisis pasar Saham Indonesia - Muhammad Thareq Kemal; Fakhruddin Fakhruddin (Syiah Kuala University, 2015)
This research aimed to analyze the interaction between IHSG, portfolio investment, BI rate and exchange rate to understand which variable has more dominant factors onto the others. Restricted VAR was employed to test the hypothesis. Data was quarterly from 1997:Q3 to 2013:Q4. The empirical results showed that all variables have bi-directional causality. More significant correlation could be observed between IHSG and portfolio investment and exchange rate; portfolio investment is significantly correlated with IHSG, BI rate and exchange rate; BI rate has significant effect on the volatility of IHSG and portfolio investment; and exchange rate significantly affected portfolio investment. Monetary policies was considered effective to affect IHSG, portfolio investment and exchange rate, implying that the authority should maintain the stability of BI rate.